American Silent Horror, Science Fiction and Fantasy Feature Films, 1913-1929. - Soister, John T. (McFarland & amp; Company, Inc., Publishers, 2012)
During the Silent Era, when most films dealt with dramatic or comedic takes on the "boy meets girl, boy loses girl" theme, other motion pictures dared to tackle such topics as rejuvenation, revivication, mesmerism, the supernatural and the grotesque. A Daughter of the Gods (1916), The Phantom of the Opera (1925), The Magician (1926) and Seven Footprints to Satan (1929) were among the unusual and startling films containing story elements that went far beyond the realm of "highly unlikely." Using surviving documentation and their combined expertise, the authors catalog and di.